2021
DOI: 10.3390/microorganisms9102132
|View full text |Cite
|
Sign up to set email alerts
|

Scalp Microbiome and Sebum Composition in Japanese Male Individuals with and without Androgenetic Alopecia

Abstract: The skin microbiome and sebum may be associated with inflammation-related diseases of the scalp. To assess the pathogenesis and progression of androgenetic alopecia (AGA), we analyzed the composition of sebum and the bacterial and fungal microbiomes of the scalps of 118 Japanese male individuals with and without AGA, then discussed their roles in the pathogenesis of AGA. Sebum triglyceride and palmitic acid contents were higher in the AGA group than in the non-AGA group. Malassezia restricta, a lipophilic fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 52 publications
(53 reference statements)
2
20
1
1
Order By: Relevance
“…Several scientific published evidence have reported the strict correlation between microbial disequilibrium and skin conditions [ 4 , 5 , 7 , 8 , 9 , 10 ]. Given this growing body of literature, it is becoming increasingly clear that the modulation of the microbiota may be a novel and important adjunct modality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several scientific published evidence have reported the strict correlation between microbial disequilibrium and skin conditions [ 4 , 5 , 7 , 8 , 9 , 10 ]. Given this growing body of literature, it is becoming increasingly clear that the modulation of the microbiota may be a novel and important adjunct modality.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of AA was evaluated based on the extent of scalp hair loss, progression of disease, and response of treatment, and was divided into mild AA ( n = 26) and severe AA ( n = 7) ( Table 1 ). The scalp samples were obtained by means of swab procedure according to previously reported methods [ 8 , 9 , 10 ] with minor modifications. Sterile cotton swabs were soaked for at least 30 s in solution (0.9% NaCl and 0.1% Tween 20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent analysis of the scalp fungal microbiome revealed that the relative abundance and scalp colonization level of the lipophilic fungus Malassezia were higher in patients with AGA than in individuals without AGA. Therefore, Malassezia may be involved in the development or exacerbation of AGA 4 …”
Section: Figurementioning
confidence: 99%
“…The colonization levels of all Malassezia species were obtained from our previous report 4 . M. globosa and M. restricta colonization levels were further examined in the present study.…”
Section: Figurementioning
confidence: 99%